2019
DOI: 10.1364/boe.10.005650
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oviduct ciliary beat frequency using real time phase resolved Doppler spectrally encoded interferometric microscopy

Abstract: Ciliary activity, characterized by the coordinated beating of ciliary cells, generates the primary driving force for oviduct tubal transport, which is an essential physiological process for successful pregnancies. Malfunction of the cilium in the fallopian tube, or oviduct, may increase the risk of infertility and tubal pregnancy that can result in maternal death. While many ex-vivo studies have been carried out using bright field microscopy, this technique is not feasible for the in-vivo investigation of ovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In 2017, Lan et al reported a high-phasestability OCE system using a common-path spectraldomain OCT (SD-OCT) to achieve a subnanometre displacement sensitivity, demonstrating the feasibility of common-path OCE; however, only phantom experiments were performed 19 . In addition, SD-OCT-based OCE systems are based on a static operation principle that provides phase-stable detection 15,[20][21][22][23][24] , but their performance is limited by the groove density of the diffraction grating, the center wavelength of the light source, and the resolution of the line-scan camera, hence the inherent disadvantages of phase washout, low imaging speed, shallow penetration depth, and short imaging range 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Lan et al reported a high-phasestability OCE system using a common-path spectraldomain OCT (SD-OCT) to achieve a subnanometre displacement sensitivity, demonstrating the feasibility of common-path OCE; however, only phantom experiments were performed 19 . In addition, SD-OCT-based OCE systems are based on a static operation principle that provides phase-stable detection 15,[20][21][22][23][24] , but their performance is limited by the groove density of the diffraction grating, the center wavelength of the light source, and the resolution of the line-scan camera, hence the inherent disadvantages of phase washout, low imaging speed, shallow penetration depth, and short imaging range 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our SEIM data was processed similarly to previous studies. 13 We used the Hilbert Transform to create the analytical form of the raw SEIM data. From this, the phase term can be extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Spectrally encoded interferometric microscopy (SEIM) can detect displacement on the nanometer scale at a kilohertz frame rate and when coupled with a wavelength-swept laser and a spectral disperser, SEIM can image tissue en face. 13 Our group developed a SEIM system based on a swept source OCT system using a vertical-cavity surface emitting laser (VCSEL) with the intention of eventually measuring functional parameters of cilia across the surface of upper airway tissues. In this study, we aim to validate this SEIM system as a means of measuring ciliary beat frequency in ex vivo human upper airway tissue with high-speed video of phasecontrast microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In some species as horses, rats and hamsters only embryos are transported to uterus, unfertilized eggs are retained in oviduct (Li and Winuthayanon, 2017). Failure to capture oocyte and embryo transport (He et al, 2019).…”
Section: Discussionmentioning
confidence: 99%